2013
DOI: 10.1371/journal.pone.0053809
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Workers, Male Circumcision and HIV: A Qualitative Study of Their Understanding, Experience, and HIV Risk in Zambia

Abstract: Several sub-Saharan African countries, including Zambia, have initiated national voluntary medical male circumcision (MC) programs to reduce HIV incidence. In-depth interviews were conducted with twenty female sex workers (FSWs) in Lusaka to examine their understanding of MC and experiences with circumcised clients. Knowledge of MC was derived primarily through informal sources, with very few FSWs reporting exposure to MC educational campaigns. MC was not widely believed to be protective against HIV, however i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
(23 reference statements)
1
21
0
Order By: Relevance
“…[ 60 63 ] Three studies each were conducted in Mozambique[ 64 66 ] and Nigeria. [ 67 69 ] Two studies each were conducted in Uganda,[ 70 , 71 ] Zambia,[ 72 , 73 ] and Zimbabwe. [ 51 , 74 ] One study each was conducted in Ghana,[ 75 ] Madagascar,[ 76 ] Swaziland,[ 77 ] and Tanzania,[ 78 ] Some studies were conducted in more than one country.…”
Section: Resultsmentioning
confidence: 99%
“…[ 60 63 ] Three studies each were conducted in Mozambique[ 64 66 ] and Nigeria. [ 67 69 ] Two studies each were conducted in Uganda,[ 70 , 71 ] Zambia,[ 72 , 73 ] and Zimbabwe. [ 51 , 74 ] One study each was conducted in Ghana,[ 75 ] Madagascar,[ 76 ] Swaziland,[ 77 ] and Tanzania,[ 78 ] Some studies were conducted in more than one country.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one of these participants reported longer complete wound healing, possibly as a result. Non-adherence to the recommended healing period has also been reported elsewhere [13,[28][29][30]. In a study by Herman-Roloff et al in Kenya, men who reported that their sexual partners were pleased with their circumcision decision were more likely to engage in sex within the healing period [30].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the Rwanda Zambia HIV Research Group (RZHRG) is enrolling HIV negative female sex workers (FSWs) in a longitudinal study in Zambia in preparation for a mock vaccine trial. These populations are at high risk of HIV acquisition in sub-Saharan Africa [ 26 ] where annual incidence ranges from 4-11 % for FSWs [ 27 30 ]. HIV prevalence among Zambian FSWs is estimated at 65-69 % [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%